Theoretical investigation of the water splitting mechanism on transition metal oxide catalysts - Hewa Dewage, Amendra Fernando (Kansas State University, 2016)
Water oxidation can be considered as the ‘holy grail’ of renewable energy research, where water is split into constituent molecular hydrogen and oxygen. Hydrogen is a very efficient energy source that is both clean and sustainable. The byproduct of hydrogen combustion is water, which in turn can be reused as the source for hydrogen generation. Natural water splitting is observed during photosynthesis in the oxygen-evolving complex of photosystem II, which consists of a CaMn₄O₄ cubane core. Herein, we report in silico approaches to understand bottom up catalytic design of model transition metal oxide complexes for water splitting. We have employed density functional theory to investigate model ligand-free architectures of cobalt and manganese oxide dimer (Mn₂(μ-OH)(μ-O)(H₂O)₃(OH)₅, Mn₂(μ-OH)₂(H₂O)₄(OH)₄, Mn₂(μ-OH)₂(H₂O)₂(OH)₂(O(CH)₃O)₂, Co₂(μ-OH)₂(H₂O)₄(OH)₄ and cubane (Co₄O₄(H₂O)₈(OH)₄, Mn₄O₄(H₂O)[subscript]x(OH)[subscript]y x = 4-8, y = 8-4) complexes. The thermodynamically lowest energy pathway on the cobalt dimer catalyst proceeds through a nucleophilic attack of a solvent water molecule to a Co(V)-O radical moiety whereas the pathway on the cubane catalyst involves a geminal coupling of a Co(V)-O radical oxo group with bridging oxo sites. The lowest energy pathway for the fully saturated Mn₂O₄•6H₂O (Mn₂(μ-OH)(μ-O)(H₂O)₃(OH)₅) and Mn₂O₃•7H₂O (Mn₂(μ-OH)₂(H₂O)₄(OH)₄) complexes occur through a nucleophilic attack of a solvent water molecule to Mn(IV½)O and Mn(V)O oxo moieties respectively. Out of all the oxidation state configurations studied for the manganese cubane, we observed that Mn₄(IV IV IV IV), Mn₄(III IV IV IV), and Mn₄(III III IV V) configurations are thermodynamically viable for water oxidation. All three of these reaction pathways proceed via nucleophilic attack of solvent water molecule to the manganese oxo species. The highest thermodynamic energy step in manganese dimer and cubane complexes corresponds to the formation of the manganese oxo species, which is a significant feature that reoccurred in all these reaction pathways. We have also employed multireference and multiconfigurational calculations to investigate the Mn₂(μ-OH)₂(H₂O)₂(OH)₂(O(CH)₃O)₂ system. The presence of Mn(IV)O[superscript]• radical moieties has been observed in this catalytic pathway. These simplest models of cobalt and manganese with water-derived ligands are essential to understand microscopic properties that can be used as descriptors in designing future catalysts.
Keywords: Catalysts; Metal Oxides; Density Functional TheoryWater Splitting; Physical Chemistry (0494)